Iraqi Militia’s January 2024 Attacks on US Military Bases: Insights from 'Unrestricted Warfare' Theory - Filip Banáš (Obrana a Strategie)
This study examines the January 2024 attacks by Shi’a Iraqi militias on US military bases in Jordan through the lens of the 'Unrestricted Warfare' theory, highlighting the volatile dynamics of US-Iranian relations and Iran’s influence over its affiliated militias. It explores the militias’ operational behaviors, contextualized within Middle Eastern geopolitics and the broader implications of hybrid warfare strategies. Employing David Kilcullen's theoretical framework, the article underscores how varying boundaries of warfare exacerbates regional tensions, risking escalation into broader conflict. The findings emphasize the need for a nuanced understanding of Iranian-militia relations and their implications for US foreign policy in preventing all-out war.